Label-free quantitative proteome analysis of the surface-bound salivary pellicle - Delius, Judith; Trautmann, Simone; Médard, Guillaume; Kuster, Bernhard; Hannig, Matthias; Hofmann, Thomas (Colloids and surfaces, B, Biointerfaces, 2017)
[Display omitted] •Salivary proteins at the saliva-tooth interface adsorb selectively to the solid substratum.•The pellicle’s proteome reveals a high inter-day and inter-individual consistency.•The surface enriched pellicle proteins are particularly enzymes and immune response proteins. The salivary pellicle, covering natural as well as restored tooth surfaces in the oral cavity as an immobilized protein-rich layer, acts as an important physico-chemical and biological mediator at the tooth-saliva-interface. For the first time, the pellicle’s proteome of individual volunteers were analyzed separately on three consecutive days and the relative protein abundance determined by a label-free quantitative nano-LC–MS/MS approach. A total of 72 major proteins were identified in the initial pellicles formed intraorally on dental ceramic specimens already after 3min with high inter-individual and inter-day consistency. In comparison, significant differences in protein abundance were evident between subjects, thus indicating unique individual pellicle profiles. Furthermore, the relative protein abundance in pellicles was compared to the proteome pattern in the corresponding saliva samples of the same individuals to provide first data on significantly enriched and depleted salivary proteins (p <0.05) within the surface-bound salivary pellicle. Our findings reveal the initial adsorption of salivary proteins at the solid-liquid interface to be a rapid, highly selective, and reproducible process leading to the immobilization of a broad range of protective proteins and enzymes on the substratum surface within a few minutes. This provides evidence that the pellicle layer might be physiologically functional even without further maturation.